2020
DOI: 10.1016/j.jvscit.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Snare-assisted thoracic endovascular aortic repair for redirection of a false lumen elephant trunk

Abstract: In recent years, a hybrid approach to the classic two-stage elephant trunk technique has come into favor for treatment of thoracic aortic dissection. During the first stage, inadvertent intraoperative placement of the elephant trunk into the false lumen can occur on rare occasions, resulting in untoward difficulties during the second stage of the procedure. We describe here a snare-assisted technique for endovascular salvage of an elephant trunk that had inadvertently been placed in the false lumen of a chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…To manage this complication nonemergently, the FL and TL should be bridged using existing or new trans-septal fenestrations. 5 Fenestrations can be created via a guidewire or an atraumatic radiofrequency wire and serially balloon dilated or using an Outback LTD re-entry catheter (Cordis, Johnson & Johnson, Bridgewater, NJ). 4 , 5 , 6 , 7 , 8 For more acute dissections, the thin flap architecture can be perforated or torn down using a micro-guidewire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To manage this complication nonemergently, the FL and TL should be bridged using existing or new trans-septal fenestrations. 5 Fenestrations can be created via a guidewire or an atraumatic radiofrequency wire and serially balloon dilated or using an Outback LTD re-entry catheter (Cordis, Johnson & Johnson, Bridgewater, NJ). 4 , 5 , 6 , 7 , 8 For more acute dissections, the thin flap architecture can be perforated or torn down using a micro-guidewire.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Fenestrations can be created via a guidewire or an atraumatic radiofrequency wire and serially balloon dilated or using an Outback LTD re-entry catheter (Cordis, Johnson & Johnson, Bridgewater, NJ). 4 , 5 , 6 , 7 , 8 For more acute dissections, the thin flap architecture can be perforated or torn down using a micro-guidewire. 9 We used an existing fenestration proximal to the ET and the ascending aorta–femoral snare-assisted technique to bridge the first-stage TEVAR and the ET using a stent.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Chen et al reported that inadvertent placement of an elephant trunk into the FL was repaired by implantation of a stent graft using a right-brachial to femoral through-and-through wire approach. 9 A femoral guidewire was advanced from the TL into the FL via a preexistent intimal tear without necessity for fenestration. Snaring of the wire from an additional transbrachial access secured successful FL-TL redirection.…”
Section: Discussionmentioning
confidence: 99%